Using Logico Media to Enhance Students' Speaking Skills in Report Texts - Syaifullah; Kristini (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
Research on the use of Logico media to improve students' speaking skills in report text for high school students is still rarely done. Therefore, the purpose of this research is to describe and evaluate the effectiveness of Logico media in improving English proficiency in Report Text in class IX students of Room 1 MTs Negeri (State Islamic junior high school) 1 Kotawaringin Timur. This type of research is Classroom Action Research which is carried out in two cycles. Each cycle consists of 3 meetings with research procedures starting from planning, implementing, observing, and reflecting. The subjects of this study were 31 students of Class IX Room 1 MTs Negeri 1 Kotawaringin Timur. The data in this study were obtained through tests, observations, interviews, and documentation. The data were then descriptively, quantitatively, and qualitatively analyzed. This study's findings show that Logico Media helps students in Room 1 of MTs Negeri 1 Kotawaringin Timur's Class IX improve their speaking skills and learning outcome. English-speaking skills increased from 19.84 percent to 85.64 percent by the end of cycle 2, while classical learning outcomes reached 100% with a percentage increase from 48.39 percent to 100 percent by cycle 2